1999
DOI: 10.1002/1531-8249(199901)45:1<40::aid-art8>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Region-specific encoding of sensory and affective components of pain in the human brain: A positron emission tomography correlation analysis

Abstract: Brain imaging with positron emission tomography has identified some of the principal cerebral structures of a central network activated by pain. To discover whether the different cortical and subcortical areas process different components of the multidimensional nature of pain, we performed a regression analysis between noxious heat‐related regional blood flow increases and experimental pain parameters reflecting detection of pain, encoding of pain intensity, as well as pain unpleasantness. The results of our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
142
2
13

Year Published

2000
2000
2009
2009

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 351 publications
(170 citation statements)
references
References 40 publications
10
142
2
13
Order By: Relevance
“…Thus, lesions to the dorsal portion of the ACC (dACC) (4) or insula (5) result in patients reporting that they are no longer bothered by painful stimulation even though they can still perceive it. Similarly, neuroimaging studies have shown that the dACC tracks the affective component of pain (6) and is closely correlated with perceived pain unpleasantness (7)(8)(9). Analogous results have been found for the anterior insula, particularly with respect to chronic pain (10).…”
mentioning
confidence: 64%
“…Thus, lesions to the dorsal portion of the ACC (dACC) (4) or insula (5) result in patients reporting that they are no longer bothered by painful stimulation even though they can still perceive it. Similarly, neuroimaging studies have shown that the dACC tracks the affective component of pain (6) and is closely correlated with perceived pain unpleasantness (7)(8)(9). Analogous results have been found for the anterior insula, particularly with respect to chronic pain (10).…”
mentioning
confidence: 64%
“…imaging studies showing more than one pain-evoked activation focus with different stimulus-response functions within ACC (45)(46)(47)(48)(49). These activation foci are located in anterior as well as in posterior regions of the ACC.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that this was a direct morphological correlate for the occurrence of nerve-mediated effects in this region. Indicating a sensitization of sensory afferents (nociceptors) to mechanical stimuli, local pain may persist even after the initial irritation has disappeared [56]. Use of a local anesthetic has been shown to alter local release of neuropeptides [5,29,39,49].…”
Section: Discussionmentioning
confidence: 99%